2021
DOI: 10.5041/rmmj.10451
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus and Cancer Stem Cell markers in Oral Epithelial Dysplasia—An Immunohistochemical Study

Abstract: Objectives: To study the correlation between the putative cancer stem cell (CSC) markers aldehyde dehydrogenase 1 (ALDH1), cluster of differentiation 44 (CD44), sex-determining region Y-box 2 (SOX2), and octamer-binding protein 4 (OCT4) and human papilloma virus (HPV) infection using p16, the surrogate marker of HPV in oral epithelial dysplasia (OED) and normal mucosa. Methods: Five sections each from 40 histopathologically diagnosed cases of different grades of OED and 10 cases of normal oral mucosa without d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It was observed that the Ki-67 protein increased with advancing grades of OSCC which was also consistent with earlier research [23][24][25][26][27][28]. Nuclear Ki-67 positivity was identified in the peripheral region of tumor islands in well-differentiated OSCC.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It was observed that the Ki-67 protein increased with advancing grades of OSCC which was also consistent with earlier research [23][24][25][26][27][28]. Nuclear Ki-67 positivity was identified in the peripheral region of tumor islands in well-differentiated OSCC.…”
Section: Discussionsupporting
confidence: 90%
“…This was in line with earlier research [ 23 , 24 ]. The rate of malignant transformation may be influenced by the degree of dysplasia, with high-grade dysplastic lesions being 4.5 times more likely to undergo such transformation than low-grade dysplastic lesions [ 23 - 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations